2021
DOI: 10.3389/fneur.2020.584479
|View full text |Cite
|
Sign up to set email alerts
|

Can Extra Daytime Light Exposure Improve Well-Being and Sleep? A Pilot Study of Patients With Glaucoma

Abstract: Glaucoma damages retinal ganglion cells, including intrinsically photosensitive retinal ganglion cells (ipRGCs). These cells modulate various non-visual physiological and psychological functions which are modulated by light. In patients with glaucoma, we assessed the effect of daily bright light exposure (LE) on several melanopsin-dependent functions, such as the pupil constriction, circadian rest-activity cycles, sleep and subjective well-being including relaxation, alertness and mood. Twenty patients partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…[45], it was observed that exposure to high levels of lighting in the morning was associated with reduced sleep onset latency, increased phasor magnitudes (which is a measure of circadian entrainment), and increased sleep quality in adult participants. These ndings were aligned with other similar inquiries on other age groups [46][47][48]. Whereas there is growing evidence for circadian relevance in migraine and other pain disorders [21,49], none of the previous studies were focused on circadian effects of light on patients with migraine with photosensitivity.…”
Section: Discussionsupporting
confidence: 81%
“…[45], it was observed that exposure to high levels of lighting in the morning was associated with reduced sleep onset latency, increased phasor magnitudes (which is a measure of circadian entrainment), and increased sleep quality in adult participants. These ndings were aligned with other similar inquiries on other age groups [46][47][48]. Whereas there is growing evidence for circadian relevance in migraine and other pain disorders [21,49], none of the previous studies were focused on circadian effects of light on patients with migraine with photosensitivity.…”
Section: Discussionsupporting
confidence: 81%
“…As most human beings have a circadian period slightly longer than 24 h [ 147 ], morning light is needed to advance the clock and favour earlier sleep times, and so morning light is typically considered beneficial. Whether more light in the morning can rebalance excessive evening light exposure to improve mood, sleep, and well-being is currently under investigation [ 148 ].…”
Section: Emotional Processing and Moodmentioning
confidence: 99%
“…Furthermore, light and the extent of the day-night intensity differences modulate chronotype, sleep parameters, and circadian alignment [24][25][26][27][28]. This also occurs in glaucoma [29]. Seasonal differences in serum lipids [30,31] can in part be accounted for by differences in ambient light conditions [32,33].…”
Section: Introductionmentioning
confidence: 99%